Social problems in health, housing, and education of the afro-descendent community in the department of Cordoba Colombia - Restrepo Jimenez, Luis Carlos; Restrepo Jimenez, Luis Carlos; Restrepo Jimenez, Luis Carlos (Corporación Universitaria Americana, 2021)
Introduction: Afro-Colombian communities in our country have been subjected to violations of their rights for decades, so much so that this phenomenon is reflected in the statistics of the different censuses carried out throughout the territory. Objective: For this reason the objective of this article of reflection seeks to verify the state of the question, taking information from 2005 to 2015, aimed at the entire community in genera  getting to know more closely the situation that Af ros are experiencing. in Colombia and the cordoba department , in aspects as relevant as Health, Education, Housing, and then in a second study to verify that so much progress has been made up to the present. Method or methodology: in order to identify the problem, this researcher makes a documentary review and bibliographic consultation of primary and secondary sources that lead to the punch line of the objective. Consequently, as a result, it was possible to bring up the identification of policies, recommendations and causes that different international, state and private organizations have been working on in these aspects in order to design a solution proposal that allows improving the situation of marginality and inclusion of historically the aforementioned communities have been victims. Conclusions and results: Finally, with respect to aspects related to culture, race and customs, these communities continue to be mistreated, a phenomenon that has had an evolutionary behavior in most nations, in what has been human evolution.